PERAN PENDIDIKAN KEWIRAUSAHAAN DALAM PEMBERDAYAAN MASYARAKAT MISKIN DI INDONESIA - Sukidjo Sukidjo (Jurnal Economia, 2012)
Abstract: The Role of Entrepreneurship Education in the Empowerment of the Poor in Indonesia. Poverty has become an international problem. Poverty reduction effort is a major commitment of all countries that have ratified the Millennium Development Goals. The nature of poverty involves many aspects such as economic, political, and social and cultural. Therefore, poverty reduction programs consisting of financial/economic support as well as empowerment program i.e. entrepreneurship education. This empowerment program focuses on shaping an independent mental attitude, creative, and persistent so that the individuals’ potential and provided facilities can be utilized optimally. Furthermore, “the charity programs” should be addressed specific to the poor who are elderly.